Developments in the assessment of non-motor disease progression in amyotrophic lateral sclerosis. (2nd December 2021) - Chiò, Adriano; Canosa, Antonio; Calvo, Andrea; Moglia, Cristina; Cicolin, Alessandro; Mora, Gabriele
ABSTRACT: Introduction: The burden of non-motor symptoms is a major determinant of quality of life and outcome in amyotrophic lateral sclerosis (ALS) and has profound negative effect also on caregivers. Areas covered: Non-motor symptoms in ALS include cognitive impairment, neurobehavioral symptoms, depression and anxiety, suicidal ideation, pain, disordered sleep, fatigue, weight loss and reduced appetite, and autonomic dysfunctions. This review summarizes the measures used for the assessment of non-motor symptoms and their properties and recaps the frequency and progression of these symptoms along the course of ALS. Expert opinion: Non-motor symptoms in ALS represent a major component of the disease and span over several domains. These symptoms require a high level of medical attention and should be checked at each visit using ad hoc questionnaires and proactively treated. Several instruments assessing non-motor symptoms have been used in ALS. Specific screening questionnaires for non-motor symptoms can be used for monitoring patients during telehealth visits and for remote surveillance through sensors and apps installed on smartphones. Novel trials for non-motor symptoms treatment specifically designed for ALS are necessary to increase and refine the therapeutic armamentarium. Finally, scales assessing the most frequent and burdensome non-motor symptoms should be included in clinical trials.